2010
DOI: 10.1038/onc.2010.349
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative interactions of PTEN deficiency and RAS activation in melanoma metastasis

Abstract: Summary MAPK and AKT pathways are frequently co-activated in melanoma through overexpression of receptor tyrosine kinases, mutations in their signaling surrogates, such as RAS and BRAF, or loss of negative regulators such as PTEN. Since RAS can be a positive upstream regulator of PI3-K, it has been proposed that the loss of PTEN and the activation of RAS are redundant events in melanoma pathogenesis (Tsao et al., 2000). Here, in genetically engineered mouse models of cutaneous melanomas, we sought to better un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 52 publications
(70 reference statements)
3
88
0
Order By: Relevance
“…[35][36][37] On the other hand, although RAS is a potent oncogene, its tumorigenicity depends on the cellular context and cooperative events and previous reports have shown that expression of PTEN is suppressed by the oncogenic RAS via the RAF/ERK/MEK signaling pathway giving rise to cells with greater malignant potential. [38][39][40][41][42] The localization of PTEN has not been assessed in these studies although accumulating genetic, pathologic and biochemical evidence suggests that the localization of PTEN either in the nucleus or cytoplasm affects the proliferation of tumor cells. [43][44][45][46][47] In the current study, it was found that loss of PTEN nuclear expression in metastases was significantly associated with KRAS mutations; this finding is in accordance with a mechanism of suppression of PTEN nuclear translocation through KRAS activation.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] On the other hand, although RAS is a potent oncogene, its tumorigenicity depends on the cellular context and cooperative events and previous reports have shown that expression of PTEN is suppressed by the oncogenic RAS via the RAF/ERK/MEK signaling pathway giving rise to cells with greater malignant potential. [38][39][40][41][42] The localization of PTEN has not been assessed in these studies although accumulating genetic, pathologic and biochemical evidence suggests that the localization of PTEN either in the nucleus or cytoplasm affects the proliferation of tumor cells. [43][44][45][46][47] In the current study, it was found that loss of PTEN nuclear expression in metastases was significantly associated with KRAS mutations; this finding is in accordance with a mechanism of suppression of PTEN nuclear translocation through KRAS activation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, tumors that lacked Ras mutations also had complete loss of Pten as a result of deletion of the wild-type allele. However, this has recently been contradicted by a study that found that ~14% of human melanomas that had an N-RAS mutation also harbored PTEN loss (Nogueira, Kim et al 2010). A subsequent mouse model of Tyr-HRAS V21G ink4a/Arf-/-in a Pten+/+ or Pten+/-background showed that inactivation of one copy of Pten led to earlier onset of melanoma whereas mice lacking expression of activated Ras in the Pten+/-Ink4aArf-/-did not develop melanoma establishing that activation of Ras and loss of Pten cooperates in a subset of melanomas (Nogueira, Kim et al 2010).…”
Section: Ptenmentioning
confidence: 76%
“…199 Combination of IL-24 and erlotinib inhibited melanoma viability by inducing caspase-3 and -9 cleavage, and downregulating phosphorylated EGFR and pAkt. 199 Although these data demonstrate efficacy of this combination in preclinical 32 Functional significance of Akt1 is yet to be established in melanomas. Therefore, it is important to establish the role of each Akt isoform before testing a pharmacological agent in the clinic, particularly since any of the three isoforms has the theoretical potential to promote metastasis.…”
Section: Strategies To Overcome Drug Resistancementioning
confidence: 99%
“…31 In addition, loss of PTEN increased melanoma cell invasion and migration by shifting the phosphorylation status from Akt3 to Akt2 and by downregulating E-cadherin. 32 Therefore, an unanswered question remains as to why inhibiting PTEN exerts differential effects on Akt3 and Akt2 activities in melanomas.…”
Section: Do Not Distributementioning
confidence: 99%
See 1 more Smart Citation